Erased from space and consciousness : Israel and the depopulated Palestinian villages of 1948 - Kadman, Noga (Indiana University Press, 2015)
"Hundreds of Palestinian villages were left empty across Israel when their residents became refugees after the 1948 war. Most of these villages were razed by the new State of Israel, their lands and property confiscated, but in dozens of others, communities of Jews were settled--many refugees in their own right. The state embarked upon a systematic effort of renaming and remaking the landscape, and the Arab presence was erased from official maps and histories. While most Israelis are familiar with the walls, ruins, and gardens that mark these sites today--almost half are located within tourist areas or national parks--they are unaware that Arab communities existed there within living memory. Using official documents, kibbutz publications, and visits to the former village sites, Noga Kadman reconstructs this history of erasure for all 418 depopulated villages. This is essential reading for anyone who wants to understand the Israeli-Palestinian conflict and contemporary Israeli society"--Provided by publisher.